Experimental and quantitative observational research in fencing and wheelchair fencing: A scoping review - Katharine Holmes; Lindsay Bottoms (PLoS ONE, 2026)
Background Fencing and wheelchair fencing are Olympic and Paralympic sports with growing global participation and increasing scientific interest. However, the overall structure, methodological profile, and thematic distribution of experimental and quantitative observational research in both has not been systematically characterized. Objective To map the scope, methodological characteristics, and thematic focus of experimental and quantitative observational studies involving fencing and wheelchair fencing athletes. Methods A scoping review was conducted in accordance with PRISMA-ScR guidelines. PubMed, Scopus, and EBSCOhost were searched for studies containing the terms “fencing,” “fencer,” or “fencers” in the title or abstract. Eligible studies employed experimental or quantitative observational designs and included fencing athletes as participants. Data were extracted using a structured framework and summarized descriptively across study design, research domain, participant characteristics, sample size, weapon discipline, and geographic distribution. Results A total of 445 studies met inclusion criteria. Publication volume increased substantially after 2015. Laboratory-based (35.7%) and cross-sectional (30.3%) designs predominated, whereas prospective cohort studies (5.4%) and randomized controlled trials (4.3%) were comparatively uncommon. Performance and skill analysis constituted the largest research domain (41.1%), while injury/epidemiology (7.9%), recovery/rehabilitation (4.3%), and training load/fatigue (1.6%) research were limited. Most studies involved small sample sizes with fewer than 50 participants and focused on able-bodied athletes; wheelchair fencing was markedly underrepresented. Sex was not specified in 24.3% of studies, and weapon discipline was not reported in 44.9%. Research output was geographically concentrated in Europe and select North American and East Asian countries. Conclusions Although fencing research has expanded rapidly in recent years, it remains methodologically and thematically uneven. Greater emphasis on longitudinal and interventional designs, injury surveillance, rehabilitation research, improved reporting practices, and inclusive representation across sex, weapon discipline, geographic regions, and wheelchair athletes are necessary to strengthen the translational relevance and evidence-based development of fencing sport science.